Association between Fever during Admission and Outcome of Treatment in Tuberculous Meningitis Patients in Hasan Sadikin General Hospital Bandung - Regita A Kuswanto; Ahmad Rizal; R Raspati C Koesoemadinata (Journal of Medicine and Health, 2019)
Tuberculous meningitis (TBM) is the most common type of meningitis with a highmortality rate (20-41%). There are limited data on factors associated with outcome oftreatment, especially in Indonesia. Fever is a common inflammatory process in meningitispatients. This study aims to investigate the association between fever during admission andoutcome of treatment in TBM patients treated in the In-patient Neurology Department at HasanSadikin Hospital Bandung. This is an observational retrospective cohort study conducted byusing medical records from 2017. The inclusion criteria of this study were all medical recordsof inpatients who were diagnosed as TBM and ?18 years old, while the exclusion criteria wereincomplete medical records. The variables in this study were age, gender, body temperature,classification of TBM, and Glasglow Outcome Scale (GOS). There were 125 medical recordswhich fulfilled the inclusion criteria. Kruskal- Wallis test showed that fever was notsignificantly associated with GOS (p=0.193). In conclusion, fever during admission was notassociated with GOS in TBM patients.Keywords: tuberculous meningitis, fever, Glasglow Outcome Scale, outcome